2008
DOI: 10.1186/1472-6785-8-1
|View full text |Cite
|
Sign up to set email alerts
|

Superior infectivity for mosquito vectors contributes to competitive displacement among strains of dengue virus

Abstract: Background: Competitive displacement of a weakly virulent pathogen strain by a more virulent strain is one route to disease emergence. However the mechanisms by which pathogens compete for access to hosts are poorly understood. Among vector-borne pathogens, variation in the ability to infect vectors may effect displacement. The current study focused on competitive displacement in dengue virus serotype 3 (DENV3), a mosquito-borne pathogen of humans. In Sri Lanka in the 1980's, a native DENV3 strain associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 87 publications
3
89
1
1
Order By: Relevance
“…By comparing the ability of three DENV-3 isolates of a native lineage and three DENV-3 isolates of an invasive lineage to be transmitted by A. aegypti, Hanley et al (19) showed that a clade replacement event in Sri Lanka during the 1980s was associated with enhanced mosquito transmission potential for the invasive lineage. Enhanced transmissibility was associated with a higher body titer and an increased proportion of A. aegypti females with a disseminated infection (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the ability of three DENV-3 isolates of a native lineage and three DENV-3 isolates of an invasive lineage to be transmitted by A. aegypti, Hanley et al (19) showed that a clade replacement event in Sri Lanka during the 1980s was associated with enhanced mosquito transmission potential for the invasive lineage. Enhanced transmissibility was associated with a higher body titer and an increased proportion of A. aegypti females with a disseminated infection (19).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of DENV gene sequence data have shown that clade replacement events are sometimes associated with signals of positive natural selection, such as an increase in the rate of nonsynonymous substitutions (7), but not always (26,47). Some phylogenetic studies have concluded that major clade replacements were primarily due to stochastic events (31,47), whereas others found potentially causal differences in viral fitness between lineages, such as a higher viremia level in the human host (43) or enhanced infectivity to mosquito vectors (3,5,19).…”
mentioning
confidence: 99%
“…These cases of coinfection might be related to coinfections in the mosquito vector; however, there are also few reports about mosquito coinfections, and only a few studies have demonstrated the simultaneous existence of natural serotype 2 and 3 infections in Aedes populations from Asia and America [23,24]. Additionally, the presence of intra-host competition in the vector, which may favor the replication of some viral variants over others, has been reported for other infection models, either between two serotypes of the same virus [24] or between strains of the same serotype [25], thereby favoring the transmission of one of the variants. Similar behaviors have been reported for DENV and chikungunya virus coinfections, in which the percentages of infection spread were better for the Chikungunya virus [26].…”
Section: Introductionmentioning
confidence: 99%
“…This finding contrasts with other studies of DENV lineage invasions that showed such an advantage. 36,51,58 Notably, although other lineage/genotype replacement events associated with increased disease severity involved a period of lineage/genotype cocirculation, the southeast Asian/American lineage II viruses from our study were introduced into Loreto in the absence of any DENV-2 competitors. 59,60 It is clear that both host and viral factors can play a role in determining dengue disease severity.…”
Section: Denv-2 Lineage II Peru Outbreakmentioning
confidence: 99%
“…aegypti of the National Institutes of Health colony strain were fed for 20 minutes on blood meals composed of 2 mL washed rabbit red blood cells (Hemostat, Dixon, CA) in 10% sucrose combined with 1 mL virus offered in water-jacketed membrane feeders (Lillie Glass, Smyrna, GA) covered with a parafilm seal. 51 Virus titer in the blood meals ranged from 5.48 to 6.48 log 10 FFUs/mL. Engorged mosquitoes were separated, incubated at 28 C and 80% relative humidity on a 12-hour:12-hour light:dark cycle with ad lib access to 10% sucrose solution for 14 days, and then, frozen at −20 C overnight.…”
Section: Denv-2 Lineage II Peru Outbreakmentioning
confidence: 99%